2002
DOI: 10.1097/00000433-200212000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Siderophages and Unexpected Infant Death

Abstract: It has been proposed that the presence of siderophages in the lungs of infants who die unexpectedly should be considered a marker of a previous hypoxic event, which may preclude a diagnosis of sudden infant death syndrome. The authors retrospectively reviewed all infant deaths (<1 year old) going to autopsy at the Denver Office of the Medical Examiner from January 1999 to January 2001. Lung sections were stained with Prussian blue, and siderophages were counted in 20 high-power fields per lobe sampled. Cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 11 publications
1
28
1
Order By: Relevance
“…Whatever the mechanism of previous pulmonary haemorrhage in the NAI-related deaths in our series, we found that alveolar HLMs were significantly more common in NAI than in unexplained SUDI with no features of NAI, which is consistent with findings of previous studies [8,10,16]. The advantages of the methodology of our study are first, the large size of the study group, this being the largest study of HLMs in SUDI, all of which were examined using a common autopsy protocol at a single centre, and secondly, that no attempt was made to quantify alveolar HLM counts, such scoring systems often being subject to considerable inter-and intraobserver variability; instead, we merely reported the presence of alveolar HLMs in at least one Perls stained lung section in an otherwise unselected population of SUDI referred to our centre for autopsy, thus removing potential subjective bias in the interpretation of the extent and/or severity of HLMs/haemosiderin content on histological examination of the lungs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Whatever the mechanism of previous pulmonary haemorrhage in the NAI-related deaths in our series, we found that alveolar HLMs were significantly more common in NAI than in unexplained SUDI with no features of NAI, which is consistent with findings of previous studies [8,10,16]. The advantages of the methodology of our study are first, the large size of the study group, this being the largest study of HLMs in SUDI, all of which were examined using a common autopsy protocol at a single centre, and secondly, that no attempt was made to quantify alveolar HLM counts, such scoring systems often being subject to considerable inter-and intraobserver variability; instead, we merely reported the presence of alveolar HLMs in at least one Perls stained lung section in an otherwise unselected population of SUDI referred to our centre for autopsy, thus removing potential subjective bias in the interpretation of the extent and/or severity of HLMs/haemosiderin content on histological examination of the lungs.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, consistent evidence is provided by a mouse model, based on intranasal instillation of blood, in which haemosiderin staining within alveolar macrophages was first detected at day 3, peaked at day 7, and persisted through to the end of the study period after 2 months [12]. Previous studies have attempted to examine the significance of HLMs in the setting of sudden unexpected death in infancy (SUDI) and sudden infant death syndrome (SIDS), and published series in the English-language literature of pulmonary HLMs in sudden infant death are summarised in Table 2 [8,10,[14][15][16][17][18][19][20][21]. However, data comparison between different studies is hampered by inconsistent use of terminology and lack of standardised classification and scoring systems for haemosiderin content or HLMs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations